Aroma of wheat porridge and bread-crumb is influenced by the wheat variety. Issue 1 (September 2015) - Starr, G.; Hansen, Å.S.; Petersen, M.A.; Bredie, W.L.P.
Abstract Sensory evaluations were conducted on wheat-flour porridge and baked-bread samples, made from wheat varieties with known odour and flavour variations. The purpose was to determine if these odour and flavour variations were expressed in baked-bread. In all, 24 wheat varieties were used for porridge evaluation, from these eight were selected for bread evaluation. Porridge and bread results were compared. Variations were found in both evaluations. Five odour- and nine flavour descriptors were found to be common to both wheat porridge and bread. The results for two descriptors: "cocoa" and "oat porridge" were correlated between the wheat porridge and bread samples. Analysis of whole-meal and low-extraction samples revealed that the descriptors "malt", "oat-porridge", "øllebrød", "cocoa" and "grain" mostly characterized wheat bran, while descriptors for "maize", "bean-shoots", "chamomile", "umami", and "fresh grass" mostly characterized wheat endosperm. Low-extraction bread made from four different varieties also differentiated for five odour- and six flavour descriptors. These results indicate that variations in wheat flavour and odour directly affect bread flavour and odour even in low-extraction bread. This knowledge is important to the baking industry and to plant breeders as wheat aroma could possibly become a future quality parameter in breeding.